Molecular approach to a patient's tailored diagnosis of the oral allergy syndrome. Issue 1 (17th June 2020) - Alessandri, Claudia; Ferrara, Rosetta; Bernardi, Maria Livia; Zennaro, Danila; Tuppo, Lisa; Giangrieco, Ivana; Ricciardi, Teresa; Tamburrini, Maurizio; Ciardiello, Maria Antonietta; Mari, Adriano
Abstract: Oral allergy syndrome (OAS) is one of the most common IgE‐mediated allergic reactions. It is characterized by a number of symptoms induced by the exposure of the oral and pharyngeal mucosa to allergenic proteins belonging to class 1 or to class 2 food allergens. OAS occurring when patients sensitized to pollens are exposed to some fresh plant foods has been called pollen food allergy syndrome (PFAS). In the wake of PFAS, several different associations of allergenic sources have been progressively proposed and called syndromes. Molecular allergology has shown that these associations are based on IgE co‐recognition taking place between homologous allergens present in different allergenic sources. In addition, the molecular approach reveals that some allergens involved in OAS are also responsible for systemic reactions, as in the case of some food Bet v 1‐related proteins, lipid transfer proteins and gibberellin regulated proteins. Therefore, in the presence of a convincing history of OAS, it becomes crucial to perform a patient's tailored molecule‐based diagnosis in order to identify the individual IgE sensitization profile. This information allows the prediction of possible cross‐reactions with homologous molecules contained in other sources. In addition, it allows the assessment of the risk of developing more severe symptoms on the basis of the features of the allergenic proteins to which the patient is sensitized. In this context, we aimed to provide an overview of the features of relevant plant allergenic molecules and their involvement in the clinical onset of OAS. The value of a personalized molecule‐based approach to OAS diagnosis is also analyzed and discussed.